Análise da transferência de calor acoplada por condução e radiação em meios semitransparentes com aplicação ao método flash - Rodrigues, Pedro Sinval Ferreira (2013)
The emergence of new materials has generated a significant growth for determination with accuracy of your thermophysical properties. The knowledge of these properties for several kinds of materials is essential for any research or engineering project that the heat transfer is relevant, because it´s from these that the rates of heat transfer in a process can be calculated. Method flash is one that stands out most among methods for thermal characterization of materials, in that the front surface of a sample is subjected to an energy pulse of high intensity and short duration, at the same time the temperature of the back surface is measured to determine the thermal diffusivity of the material. This thesis presents a methodology to thermal characterization of semitransparent material using method flash. For this, is made an analysis of the problem of heat transfer with coupling conduction-radiation, where the simultaneous solution of energy equation and the radiative transfer equation (RTE) makes necessary. The finite volume method was used to numerically solve the energy equation and the discrete ordinates method to solve the ETR. A computer code was developed in MATLAB to solve the equations, which is tested and validated with existing cases in the literature.